Pediatric heart disease : a practical guide - Daubeney, Piers E. F. (London : Wiley-Blackwell, 2012)
A companion book to Adult Congenital Heart Disease that will concentrate on the practical management of children with heart conditions. This is aimed at general paediatricians and physicians who are responsible for ongoing management, rather than specialists concerned with acute or rare presentations. The book will be illustrated with relevant radiology scans, demonstrating which investigations are appropriate, and will provide the relevant information for the generalist on patient management for different lesions. A section on emergency management is also included. Authorship is international.
Section I. General cardiology -- 1. Epidemiology and genetics -- 2. Basic cardiac physiology -- 3. Cardiac morphology and nomenclature -- -- Section II. Clinical evaluation and investigation -- 4. History and clinical examination -- 5. Basic non-invasive investigations -- 6. Echocardiography and Doppler -- 7. Diagnostic cardiac catheterization and angiography -- 8. Advanced cardiac imaging -- -- Section III. Specific congenital heart lesions -- 9. Left-to-right shunts -- 10. Right-sided malformations -- 11. Abnormalities of left ventricular inflow and outflow -- 12. Aortic malformations, rings, and slings -- 13. Coronary artery lesions -- 14. Transposition and transposition complexes -- 15. Abnormalities of right ventricular outflow -- 16. Common mixing situations -- 17. Heterotaxy, scimitar, and arteriovenous malformations -- -- Section IV. Diseases of the peri-, endo- and myocardium -- 18. Pericardial disease and infectious endocarditis -- 19. Cardiomyopathies and acute myocarditis -- 20. Cardiac tumors -- -- Section V. Pulmonary hypertension -- 21. Primary pulmonary arterial hypertension in children -- 22. Pulmonary arterial hypertension associated with congenital heart disease (including Eisenmenger syndrome) -- -- Section VI. Rhythm disorders -- 23. Bradyarrhythmias -- 24. Tachyarrhythmias -- -- Section VII. Systemic disease with cardiovascular involvement -- 25. Rheumatic fever -- 26. Marfan syndrome and connective tissue disorders -- 27. Kawasaki disease and Takayasu arteritis -- 28. Hyperlipidemia -- 29. Systemic hypertension -- -- Section VIII. Congenital heart disease at the extremes of life -- 30. Fetal cardiology -- 31. Adult congenital heart disease -- -- Section IX. Management strategies -- 32. Principles of medical management -- 33. Catheter intervention -- 34. Principles of surgical management -- 35. Heart, lung, and heart-lung transplantation -- -- Section X. Common clinical problems in the office -- 36. Murmurs in asymptomatic patients -- 37. Syncope and presyncope -- 38. Chest pain -- 39. Palpitations -- 40. Stridor -- 41. Cyanosis and cyanotic spells -- 42. Activity restriction -- -- Appendix A. Resuscitation algorithms -- Appendix B. Glossary of terms commonly used in pediatric cardiac disease -- Appendix C. Pediatric cardiac drugs and dosages -- Appendix D. Endocarditis prophylaxis -- Appendix E. Anticoagulation guidelines.
Includes bibliographical references and index.
Print version record.
Keywords: Pediatric cardiology; Congenital heart disease in children; Heart -- Diseases; Heart Defects, Congenital; Child; Infant; HEALTH & FITNESS -- Children's Health; MEDICAL -- Pediatrics; Congenital heart disease in children; Heart -- Diseases; Pediatric cardiology; Electronic books